Single Plasmonic Oligomer Chiral Spectroscopy. Issue 14 (9th May 2018) - Karst, Julian; Strohfeldt, Nikolai; Schäferling, Martin; Giessen, Harald; Hentschel, Mario
Abstract: Chirality plays a crucial role in our everyday lives. Many biomolecules are handed and the associated biological processes rely on their handedness. Thus, chirality is investigated intensely, also because of the fundamental and inherent interest in the concept of chirality. However, virtually all studies are performed on large ensembles of chiral objects, which obstructs the contribution of the individual particle. Hence, it is highly desirable to study individual chiral objects. Here, it is shown how to measure chiroptical spectra in the visible spectral range of left‐ and right‐handed C4 symmetric single plasmonic nanoantenna ensembles, which are termed oligomers. The two‐layered oligomers are fabricated by top‐down electron beam lithography to offer a high degree of structural control. Dark‐field scattering spectroscopy as well as correlative scanning electron microscopy are utilized to study the influence of structural arrangement and individual shape on the optical properties of a single plasmonic oligomer. Even minute structural differences, which cannot be resolved in scanning electron microscopy, manifest themselves in clear differences in the chiroptical response. The results play an important role for further investigations and optimizations in design, fabrication, and measurements of single plasmonic enantiomers but also on the way toward single chiral object sensing. Abstract : The influence of structural differences on the chiroptical response of single plasmonic chiral oligomers is reported. It is shown how to measure differential scattering spectra in the visible spectral range of left‐ and right‐handed C4 symmetric single plasmonic structures. Dark‐field spectroscopy and scanning electron microscopy reveal that even minute structural differences manifest themselves in clear differences in the chiroptical response.